Making a choice? Vocational Training and Decision-Making for the Undereducated and the Unemployed in Germany and the United States - Amy D. Rose; Marion Fleige (Adult Education Research Conference, 2014)
This paper compares the German and U.S. systems of career decision-making and re-training for the unemployed. Findings indicate similar issues in terms of pedagogy and the emphasis on development of systems, but differences in organizational specifics and the factors deemed to be important.